Successful treatment of a blunt retrohepatic vena cava injury using an atriocaval shunt without sternotomy or thoracotomy: a case report - Choi, Donghwan; Seo, Dongmin; Choi, Hang Jun; Moon, Jonghwan (Frontiers in Surgery, 2023)
Retrohepatic vena cava (RHIVC) injury is often fatal and can be very difficult to manage. Total hepatic vascular isolation, a shunt, or bypass surgery is required for the surgical treatment of RHIVC injury in hemodynamically unstable patients; however, these are not easy procedures. Here, we present a case of RHIVC injury that was successfully treated by atriocaval shunt placement via a transdiaphragmatic incision without sternotomy or thoracotomy. In addition, we review the resuscitation and surgical procedures used for total hepatic vascular isolation in patients with RHIVC injury.